Evaluation of the effects of aldehydes on association colloid properties and oxidative stability in bulk oils. (15th February 2021) - Jo, Seungbeen; Lee, JaeHwan
Highlights: Aldehyde effect on physicochemical properties and oxidative stability were determined. Moisture increased as aldehyde added in soybean oil during oxidation at 50 or 100 °C. Critical micelle concentration (CMC) of phospholipid changed by added aldehyde. Added aldehydes act as prooxidants in soybean oil at 50 and 100 °C treatment. Abstract: The effects of amphiphilic aldehydes, including propanal, hexanal, and nonanal, on the critical micelle concentration (CMC) of phospholipids, moisture content, and oxidative stability in soybean oil were evaluated. The selected aldehydes are typical secondary oxidation products from unsaturated fatty acids. Moisture content increased as aldehydes were added to soybean oil during thermal oxidation at a storage temperature of 50 or 100 °C. The CMC of 1, 2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) increased as propanal and hexanal were added, whereas nonanal decreased the CMC of DOPC, which implies that aldehydes participate in forming association colloids in bulk oils. The addition of aldehydes increased the rates of lipid oxidation significantly in both 50 and 100 °C treatments ( p  < 0.05), with the effect being more evident in oils treated at 50 °C than at 100 °C. Therefore, aldehydes formed from lipid oxidation affected the association colloidal structures and oxidative stability in a bulk oil matrix.